Potret media yang digunakan untuk mendapatkan informasi MP-ASI - Tri Widayanti; Acihmah Sidauruk; Jamroni Jamroni; Sarni Anggoro; Riza Yulina Amry (Health Sciences and Pharmacy Journal, 2021)
Mother's knowledge about MP-ASI is a determining factor for practice of giving MP-ASI correctly. MP-ASI or complementary feeding is food or drink given to toddlers aged 6-24 months to meet nutritional needs other than breast milk. Information is the support needed to increase mothers' understanding of complementary feeding according to the needs of their age. The government has carried out several socializations both in print and electronic media related to MP-ASI in collaboration with several professions. This study was conducted to determine the media used by mothers of toddlers when getting information about MP-ASI. The method used was a case study on mothers of toddlers who have babies aged 6-24 months at the Posyandu, Sosromenduran Gedongtengen Region, Yogyakarta City. Sampling used total sampling with the instruments used to collect data about the media and mother's knowledge were questionnaires and questionnaires. The technique of collecting and presenting data uses descriptive statistics. The results of the study were as many as 27 people (52.94%) got information about complementary feeding from the internet, 15 people (29.41%) from television, 6 people (11.76%) from the smartphone group, 2 people (3.92 %) from newspapers, and 2 (3.92%) people from bulletin boards. Mother's level of knowledge about MP-ASI for toddlers aged 6-24 months at the Posyandu, Sosromenduran Gedongtengen Region, Yogyakarta City is in the good category with internet and television as information media that provide a lot of information about MP-ASI.